RECORD OF FOUR ADULT TAXA OF CHIRONOMIDS (DIPTERA: CHIRONOMIDAE) IN THE COMBEIMA RIVER BASIN, TOLIMA, COLOMBIA (Boletín de la Sociedad Zoológica del Uruguay, 2024)
Four adult chironomid taxa: Chironomus, Polypedilum, Cricotopus and Tanyponidae sp. were recorded from the department of Tolima (Ibagué, Colombia) for the first time. The adults were collected in 2015–2016 from three Colombian high-mountain streams. Details on findings with the notes on distribution and ecology are presented.
Keywords: Aquatic insects; High Andean streams; Light trap; Malaise trap